Albendazole treatment in laying hens: Egg residues and its effects on fertility and hatchability - Moreno Torrejon, Laura (2018)
This work characterized the egg residual concentrations of albendazole (ABZ) and its sulphoxide (ABZSO) and sulphone (ABZSO2) metabolites and evaluated their effect on egg fertility and hatchability after ABZ treatments to laying hens. Seventy hens were allocated in groups: Group-1 was the control without treatment; Group-2 received a single ABZ oral dose (10 mg/kg); Group-3, -4 and -5 were treated with ABZ in medicated feed over 7 days at 10, 40, or 80 mg kg−1 day−1, respectively. Eggs were analyzed to determine the ABZ/metabolite level by HPLC or subjected to incubation to evaluate the fertility and hatchability. Only ABZSO and ABZSO2 metabolites were quantified in egg after ABZ single oral administration with maximum concentrations of 0.47 ± 0.08 and 0.30 ± 0.07 μg/ml, respectively. ABZ and its metabolites were found in eggs after 7-day ABZ treatments. The egg residue exposure estimated as AUCs (areas under the concentration vs. time curve) were 100.5 (ABZ), 56.3 (ABZSO) and 141.3 μg hr g−1 (ABZSO2). ABZ administration did not affect the egg fertility at any dosages. Egg hatchability was not affected by ABZ treatment at 10 mg/kg in medicated feed, but it decreased when the dose was 4–8 times higher. These results should be considered when ABZ is used for deworming laying hens.